SUSTAINABLE FLAT IN MEDAN DELI WITH A FOCUS ON BIOCLIMATIC ARCHITECTURE - Harisdani, Devin Defriza; Sitindaon, Iren Fitriana (Komunitas Menulis dan Meneliti (Kolibi), 2024)
Medan City has taken measures to tackle the issue of inadequate housing by offering basic rental flats (RUSUNAWA) for low-income communities (MBR). This initiative is a response to the pressing issue of escalating land density in Medan and the emergence of slum settlements among disadvantaged residents who are unable to purchase or rent homes. Particularly in swiftly developing industrial zones, the demand for housing is on the rise. This situation is influenced not only by the local residents of Medan but also by migrant workers who come to the city to work in its industrial sectors. Nevertheless, this growth is not in harmony with Medan's climate equilibrium due to the absence of bioclimatic concepts in construction practices. To tackle this challenge, bioclimatic-concept flats emerge as a promising solution for low-income communities. These flats are crafted to offer cost-effective, eco-friendly housing, uphold energy efficiency, and provide comfort for industrial workers. Consequently, this approach also upholds the principles of synergy between structures and the environment, striving to attain an equilibrium between urban expansion and environmental sustainability in Medan.